Risk factors associated with mortality and survival of acute subdural hematoma: A retrospective study - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2019)
Background: Acute subdural hematoma (ASDH) is mostly seen after head injury and is a major cause of morbidity and mortality. We studied the risk factors for ASDH and the effects of these factors on mortality as well as on survival with 100 cases from the rural area of Anatolia region. Materials and Methods: One-hundred cases of the ASDH that had been treated surgically between 2011 and 2014, at three different health-care centers from the rural area of Anatolia region, were retrospectively reviewed. Demographic data of patients, etiology, Glasgow Coma Scale (GCS) on admission, survival, presence of comorbid disease, unilaterality or bilaterality of the hematoma, and length of stay in the Intensive Care Unit (ICU) and/or neurosurgery clinic were recorded from the patients' files. Results: The total mortality rate was 34%. Age, etiology, GCS on admission, and laterality of the hematoma (unilateral or bilateral) affected the mortality rates (P = 0.005, P = 0.001, P = 0.001, and P = 0.001, respectively). Advanced age, low GCS on admission, and bilaterality of the hematoma were related with high mortality rates (P = 0.005, P = 0.001, and P = 0.001, respectively). The presence of comorbid disease and gender had no effect on patient survival (P = 0.299 and P = 0.861). Conclusion: The most important factors affecting the mortality rate were GCS on admission, etiology, age, and laterality of the hematoma in this study. Advanced age, low GCS on admission, and bilaterality of the hematoma were related with high mortality rates. Etiology had an important role in mortality rates, especially in the pedestrian injury group.
Keywords: Acute subdural hematoma; Glasgow Coma Scale; morbidity; mortality; PROGNOSTIC-FACTORS; OUTCOMES